Analisis Butir Soal pada Buku Lembar Kerja Siswa Madrasah Tsanawiyah Kelas 7 (Maharah Kitabah) dalam Perspektif Ali Alkhuli - Khairul hasbi; Hikmah; Masrun (Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Bahasa Arab dan Dakwah Masjid Agung Sunan Ampel Surabaya, 2024)
This research discusses writing skills (maharah al-kitabah) in the context of Arabic language learning in grade 7 Madrasah Tsanawiyah. Writing is an important language skill and functions to express thoughts through writing. The aim of this research is to analyze the forms of writing skills tests applied in student worksheets, as well as to categorize the questions according to Muhammad Ali al-Khuli's perspective. This research uses a library research method with primary data sources in the form of questions on student worksheets and secondary data sources in the form of books and articles related to learning speaking and writing skills. The analysis technique used is descriptive analysis. The results of the research show that several questions in the students' worksheets, such as questions 4 and 6, are in accordance with the category of sentence writing skill tests according to al-Khuli, such as questions that test the ability to write using certain rules and questions that measure the ability to copy text. However, there are some questions that place more emphasis on other skills, such as grammar, translation and reading, so they are less appropriate in distributing writing skills. This research provides recommendations so that the questions used are more suitable for measuring students' writing abilities effectively.